Research on the presence of Chagas disease in the Peruvian Police Staff - Peralta V., Aurelio (1960)
Growing number of young men from different regions of Peru, postulate their income annually to various units of the police institution. The routine medical examination to undergo these candidates in the Department of Cardiology, Hospital Police Lima, offers opportunity to do research on some aspects of national pathology. 3 years screening for Chagas disease is performed in subjects born or derived from chagasic regions, having had occasion to use our "index of suspicion" for the diagnosis of this disease in subjects come Tacna, Moquegua, Arequipa, Madre de Dios, Amazonas and San Martin (1).